Tripartite authenticated key exchange protocol for smart grid - Shengbao WANG; Xin ZHOU; Kang WEN; Bosen WENG (Tongxin xuebao)
Most of the existing authentication schemes in the smart grid environment have the drawbacks of requiring manual participation or low performance, and thus do not meet the practical needs of smart grids.A new tripartite authenticated key exchange protocol was proposed for authentication and key establishment between three parties: smart meters, service providers and control center.The protocol was based on a physical unclonable function, which removed the drawback of requiring manual participation in the operation of the protocol.The security of the protocol was demonstrated by combining BAN logic and non-formal analysis methods.Comparing with similar representative protocols, the proposed protocol has better security and higher efficiency.